Prevalence and outcomes of pregnancies in women with HIV over a 20-year period. (1st October 2021) - Kowalska, Justyna D.; Pelchen-Matthews, Annegret; Ryom, Lene; Losso, Marcelo H.; Trofimova, Tatiana; Mitsura, Viktar M.; Khromova, Irina; Paduta, Dzmitry; Stephan, Christoph; Domingo, Pere; Bakowska, Elzbieta; Monforte, Antonella d'Arminio; et al.
Abstract : Objective: To evaluate time trends in pregnancies and pregnancy outcomes among women with HIV in Europe. Design: European multicentre prospective cohort study. Methods: EuroSIDA has collected annual cross-sectional audits of pregnancies between 1996 and 2015. Pregnancy data were extracted and described. Odds of pregnancy were modelled, adjusting for potential confounders using logistic regression with generalized estimating equations. Results: Of 5535 women aged 16 to <50 years, 4217 (76.2%) had pregnancy information available, and 912 (21.6%) reported 1315 pregnancies. The proportions with at least one pregnancy were 28.1% (321/1143) in East, 24.5% (146/596) in North, 19.8% (140/706) in West/Central, 19.3% (110/569) in Central East and 16.2% (195/1203) in South Europe. Overall 319 pregnancies (24.3%) occurred in 1996–2002, 576 (43.8%) in 2003–2009 and 420 (31.9%) in 2010–2015. After adjustment, the odds of pregnancy were lower in 1996–2002, in South, Central East and East compared to West/Central Europe, in older women, those with low CD4 + cell count or with prior AIDS, and higher in those with a previous pregnancy or who were hepatitis C virus positive. Outcomes were reported for 999 pregnancies in 1996–2014, with 690 live births (69.1%), seven stillbirths (0.7%), 103 spontaneous (10.3%) and 199 medical abortions (19.9%). Conclusions: Around 20% of women in EuroSIDA reported a pregnancy, with most pregnancies after 2002, when more effective antiretroviral therapy became available. Substantial differences were seen between European regions. Further surveillance of pregnancies and outcomes among women living with HIV is warranted to ensure equal access to care. Abstract : Supplemental Digital Content is available in the text